2023
DOI: 10.1101/2023.01.13.523886
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Building modern coexistence theory from the ground up: the role of community assembly

Abstract: Modern coexistence theory (MCT) is one of the leading methods to understand species coexistence. It uses invasion growth rates -- the average, per-capita growth rate of a rare species -- to identify when and why species coexist. Despite significant advances in dissecting coexistence mechanisms when coexistence occurs, MCT relies on a "mutual invasibility" condition designed for two species communities, but poorly defined for species rich communities. Here, we review well-known issues with this component of MCT… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 117 publications
0
6
0
Order By: Relevance
“…This type of decomposition is conceptually similar to the low-density growth rate decompositions in the quantitative coexistence theory of Chesson [Chesson, 1994, 2000, 2018]. Applications of Chesson’s theory are used extensively to evaluate the relative importance of alternative coexistence factors in empirical systems [Adler et al, 2010, Ellner et al, 2016, 2018, Spaak and Schreiber, 2023]. It will be exciting to see whether similar applications of the metapopulation growth rate decomposition can play a similar role for understanding metapopulation persistence in nature.…”
Section: Discussionmentioning
confidence: 92%
“…This type of decomposition is conceptually similar to the low-density growth rate decompositions in the quantitative coexistence theory of Chesson [Chesson, 1994, 2000, 2018]. Applications of Chesson’s theory are used extensively to evaluate the relative importance of alternative coexistence factors in empirical systems [Adler et al, 2010, Ellner et al, 2016, 2018, Spaak and Schreiber, 2023]. It will be exciting to see whether similar applications of the metapopulation growth rate decomposition can play a similar role for understanding metapopulation persistence in nature.…”
Section: Discussionmentioning
confidence: 92%
“…Nevertheless, these methodologies remained restricted to communities with a relatively low number of species. To address this limitation, Spaak and Schreiber (2023b) further advanced the approach to analyse species-rich communities. Building upon the extended theoretical foundation, Spaak, Carpentier, and De Laender (2021) have shown that fitness difference, not niche difference, limits coexistence in a single trophic level.…”
Section: Lower Trophicmentioning
confidence: 99%
“…Species without a positive invasion growth rate, as well as those that were excluded, were removed from the analysis. This simplification was necessary because computing niche and fitness differences in such complex communities is challenging (Spaak & Schreiber, 2023a). Specifically, 4 out of 115 species were removed in the summer community, and 3 out of 93 were removed in the winter community.…”
Section: Assembly In Empirical Food Websmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, niche and fitness differences are estimated to better understand coexistence and are, therefore, applied to the invasion growth rates (Carroll et al., 2011; Spaak & De Laender, 2020), as positive invasion growth rates of competing species typically imply coexistence (Spaak & Schreiber, 2023; Box 1). Additionally, the sign and magnitude of niche and fitness differences inform about the species interactions, both in quality (e.g.…”
Section: Introductionmentioning
confidence: 99%